PEMETAAN SEBARAN PENERIMA PKH, KIS APBN, DAN JAMKESDA DI KABUPATEN KENDAL - Latif Junia Angreani; Bambang Agus Herlambang; Ahmad Khoirul Anam (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Social assistance programs play an important role in improving community welfare and reducing poverty levels. This study aims to map and visualize the distribution of beneficiaries of the Family Hope Program (PKH), Health Insurance funded by the State Budget (KIS APBN), and Regional Health Insurance (Jamkesda) by sub-district in Kendal Regency using a Geographic Information System (GIS). The research method involved the use of spatial data in the form of sub-district administrative boundaries and non-spatial data on the number of social assistance beneficiaries for the years 2023 and 2024. The analysis was carried out through map digitization, attribute data integration, and thematic map visualization using QGIS software. The results indicate significant differences in the number of social assistance beneficiaries among sub-districts, and the resulting maps can support local governments in determining priority areas for more targeted social assistance distribution.